A charge pump-based power conditioning circuit for low powered thermoelectric generator (TEG) - Law, Choon Chuan (2015)
Thermoelectric generator (TEG) is a sensor that utilizes thermal gradients between cold plate and hot plate of the sensor and convert it into electricity. By having a concise and non-moving structure, the sensor attracts interest in studies to implement an autonomous self sustain system. Power generation of TEG is directly proportional to temperature gradient. Therefore, the device is dismissed when the gradient source of heat is small. This limits the aim of autonomous self sustain system when it uses human temperature as source of conversion. This paper focused on the power conditioning system for a low powered thermoelectric generator. At the same time, it also determines the viability of TEG application in human portable device by adapting body temperature as source of energy conversion. This paper reveals the feasibility of signal conditioning method for a regular TEG module using charge pump.